'A Delicate Exercise': Balancing Freedom for and Freedom from Religion in Canada: Loyola High School v Quebec (Attorney General). (15th April 2016) - Ogilvie, M H
Abstract : In Loyola High School v Quebec (Attorney General) the Supreme Court of Canada (SCC) found that a Roman Catholic high school run by the Jesuits in Montreal, could be exempted from the provincial Ethics and Religious Culture Program (ERCP), legislatively mandated for all schools in Quebec, whether public or private, provided it offered an 'equivalent program', if from a Roman Catholic perspective. In the earlier companion case, SL v Commission scolaire des Chênes, the Court held that religious parents could not claim an exemption for their children enrolled in the public schools from the same course. This discrepancy between the legal treatment of children in fee-paying religious schools and children in the public school system is one of several interesting aspects of the Loyola decision which this comment will address. Notwithstanding this discrepancy, the Court also restated its earlier observations about the nature and meaning of section 2(a), 'freedom of conscience and religion', of the Canadian Charter of Rights and Freedoms (the Charter), thereby reassuring some Canadian observers that it is committed to a more robust protection of freedom of religion than may have been surmised from its earlier freedom of religion jurisprudence. Equally interesting is that, in coming to its decision, the majority of the Court moved away from the Court's earlier approach to freedom of religion issues of applying first section 2(a) and then section 1 of the Charter, which operates as a brake on full freedom of religion, to a proportional analysis more in tune with proportionality tests for religious freedom found in English and European cases. Whether this is the start of a long-term trajectory in Canadian freedom of religion cases or a single instance remains to be seen.